Multicarrier Frequency Hopping Spread Spectrum Techniques With Quasi-Cyclic Low Density Parity Check Codes Channel Coding - Yahya, Abid (2010)
This work presents a new proposed Multicarrier Frequency Hopping Spread Spectrum (MCFH-SS) system employing Quasi-Cyclic Low Density Parity Check (QC-LDPC) codes instead of the conventional LDPC codes. A new technique for constructing the QC-LDPC codes based on row division method is proposed. The new codes offer more flexibility in terms of high girth, multiple code rates and block length. Moreover, a new scheme for channel prediction in MCFH-SS system is proposed. The technique adaptively estimates the channel conditions and eliminates the need for the system to transmit a request message prior to transmitting the packet data. The ready-to-use channel will be occupied with a Pseudonoise (PN) code and use for transmission or else, it will be banned.